2011
DOI: 10.1007/s00586-011-2119-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of standard and low-modulus cement augmentation on the stiffness, strength, and endplate pressure distribution in vertebroplasty

Abstract: Purpose Vertebroplasty restores stiffness and strength of fractured vertebral bodies, but alters their stress transfer. This unwanted effect may be reduced by using more compliant cements. However, systematic experimental comparison of structural properties between standard and low-modulus augmentation needs to be done. This study investigated how standard and low-modulus cement augmentation affects apparent stiffness, strength, and endplate pressure distribution of vertebral body sections. Methods Thirty-nine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Having greater definition of the cortical shell and trabecular bone alignment also allows a better regional representation of the load transfer through the vertebrae than the more homogenized predictions seen with the direct grayscale method. This improved agreement is much stronger than the agreement found in similar studies that used a comparable methodology to the direct grayscale method and comparable to methods that used more complex, specimen‐specific material properties for each model . The conversion between grayscale and Young's modulus was comparable to studies with similar methodologies; Robson Brown et al found an equivalent conversion factor of 0.0013/GPa (0.0009/GPa in the current study), which gives a similar average bone modulus of 0.33 GPa to that of the current study, 0.25 GPa.…”
Section: Discussionsupporting
confidence: 66%
“…Having greater definition of the cortical shell and trabecular bone alignment also allows a better regional representation of the load transfer through the vertebrae than the more homogenized predictions seen with the direct grayscale method. This improved agreement is much stronger than the agreement found in similar studies that used a comparable methodology to the direct grayscale method and comparable to methods that used more complex, specimen‐specific material properties for each model . The conversion between grayscale and Young's modulus was comparable to studies with similar methodologies; Robson Brown et al found an equivalent conversion factor of 0.0013/GPa (0.0009/GPa in the current study), which gives a similar average bone modulus of 0.33 GPa to that of the current study, 0.25 GPa.…”
Section: Discussionsupporting
confidence: 66%
“…Previous numerical predictions showed that the pillar-effect of a rigid cement 6 bolus was linked to increased bulging of the end-plates and increased pressure onto the 7 adjacent disc, and the authors hypothesized that as little as 17% of pressure increase may be 8 behind the increased occurrence of the AVF. This has also been shown in an in vitro 9 experiment (Kinzl et al, 2012a) in which authors reported notably higher endplate pressure 10 in vertebrae augmented with standard (high-stiffness) cement. Whether such load shift 11 would be minimized with decreasing the vertebral stiffness similar to that observed in our 12…”
Section: Results 17supporting
confidence: 55%
“…The resulting difference between the 8 metastatic and the elderly vertebrae upon augmentation with either cement, confirms that 9 cement contribution to strength and stiffness increases with a decrease in the bone volume 10 fraction (Table 1, Figure 6), which is also in agreement with previous studies (Heini et cement. In a previous study (Kinzl et al, 2012a) it was shown that when vertebrae without 6 endplates were filled endplate-to-endplate, the specimens with standard cement were on 7 average 47% stronger than a non-augmented control group (in our study elderly specimens 8 were 303% stronger after fracture and augmentation), and 33% stiffer (in our study 17% 9 stiffer). Furthermore, with low-modulus cement, their specimens were on average 30% 10 stronger (in our study elderly specimens were 113% stronger after fracture and 11 augmentation), and 27% stiffer (in our study 13% less stiff).…”
Section: Results 17mentioning
confidence: 71%
See 1 more Smart Citation
“…28 Thirteen percent of our cohort had a segmental kyphosis over 30°, and therefore had a particularly higher risk of adjacent-segment fracture according to the study by Spross et al 28 It is known that the cemented vertebra alters the modulus of stiffness. 8,11,16 Consequently, some authors suggested the prophylactic adjacent vertebral body cementation of adjacent levels to have a protective effect. 2 In all our osteoporotic patients and in 1 traumatic patient with osteopenic bone, an additional cement augmentation of the adjacent levels was performed to prevent a cutting through of the cannulas when applying the lordotic momentum.…”
Section: Discussionmentioning
confidence: 99%